2023
DOI: 10.1002/ange.202217526
|View full text |Cite
|
Sign up to set email alerts
|

Rational Design of Ferroelectric 2D Perovskite for Improving the Efficiency of Flexible Perovskite Solar Cells Over 23 %

Abstract: Despite the great progress of flexible perovskite solar cells (f-PSCs), it still faces several challenges during the homogeneous fabrication of high-quality perovskite thin films, and overcoming the insufficient exciton dissociation. To the ends, we rationally design the ferroelectric two-dimensional (2D) perovskite based on pyridine heterocyclic ring as the organic interlayer. We uncover that incorporation of the ferroelectric 2D material into 3D perovskite induces an increased builtin electric field (BEF), w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 66 publications
(87 reference statements)
0
2
0
Order By: Relevance
“…The addition of 2D perovskites promotes 3D perovskites to undergo the same preferential (110) orientation with better crystallinity. They report elimination of lattice strain in 2D/3D flexible perovskite solar cells (f-PSC) with the highest PCE to date, over 23% [25].…”
Section: Lattice Strainmentioning
confidence: 99%
“…The addition of 2D perovskites promotes 3D perovskites to undergo the same preferential (110) orientation with better crystallinity. They report elimination of lattice strain in 2D/3D flexible perovskite solar cells (f-PSC) with the highest PCE to date, over 23% [25].…”
Section: Lattice Strainmentioning
confidence: 99%
“…After 1000 cycles of bending, the normalized PCE of the 2D/3D devices stabilized at 93% after about 200 bendings while the control dropped to 50% of the initial PCE. 127 Ji et al reported a broad white-light emitting ferroelectric 2D perovskite, (C 4 H 9 NH 3 ) 2 PbCl 4 , in which the origin of the emission and the ferroelectricity was attributed to the large structural distortion of the PbCl 6 octahedra. The light emission was strongly dependent on the temperature, showing no photoluminescence at 325 K, when the perovskite transitions from the ferroelectric to paraelectric phase.…”
mentioning
confidence: 99%